Investigation of sorbents for phosphorus removal - Šarko, Julita; Mažeikienė, Aušra (International Conference “Environmental Engineering”, 2020)
Nowadays, the problem of water pollution with phosphorus compounds is especially important. Wastewater treatment plants do not always meet the strict requirements for the residual total phosphorus concentration – 1 mg/l in the treated wastewater. Usually individual wastewater treatment plants have a poorer removal of phosphorus from the wastewater because they are more sensitive to fluctuations in wastewater flow and environmental conditions. Research results in the scientific literature shows that only 30–50% of the phosphorus is removed from the wastewater by conventional methods. Additional wastewater treatment is recommended for higher phosphorus removal efficiency achievement. One of the ways to remove phosphorus from wastewater is filtration through sorbents filter media. The efficiency of three sorbents – Filtralite P, foam-glass and crushed shells to remove phosphorus from biologically treated wastewater is investigated in this article. A phosphate phosphorus concentration was reduced by filtering wastewater through sorbents filter media during the experiment. Concentrations of treated wastewater pollutants, filtration rate, efficiency of sorbents to remove phosphorus from the wastewater were measured and evaluated. Experiment results showed that phosphate phosphorus was effectively removed by Filtralite P sorbent (removal efficiency 97–98%), less effective were foam-glass (removal efficiency 66–95%) and crushed shells sorbents (removal efficiency 39–50%).
Keywords: wastewater; phosphorus removal; Filtralite P; foam-glass; shells